Hydraulic bricolages: coexisting water supply and access regimes in N’Djamena, Chad - Ismaël Maazaz (EchoGéo)
This article investigates the ambivalent interconnectedness of water supply regimes of N’Djamena, the Chadian capital. Multiple water supply regimes coexist in N’Djamena and produce what I termed “hydraulic bricolages”. The article documents daily activities of the Technical Directorate of the Société Tchadienne des Eaux (Chad’s water national company, STE), insisting on limited available means and improvising methods that characterise hydraulic bricolages. The article then turns to alternative regimes, notably based on (cheap) water hand pumps and (costly) private boreholes. It qualifies the notion of “competing” sociotechnical regimes and stresses patterns of coexistence.